2000
DOI: 10.7863/jum.2000.19.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic measurement of tongue movement during swallowing.

Abstract: Previous ultrasonographic studies on tongue functions were limited by the possibility of artifacts caused by movement of the submental area during function. Consequently, tongue movements were misinterpreted. A dynamic tongue imaging technique, the cushion‐scanning technique, was used to overcome this problem. Later, swallowing was investigated and divided into five phases using cushion‐scanning technique‐aided M‐mode ultrasonograms. In this study, cushion‐scanning technique in combination with the B‐mode and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 14 publications
1
66
0
3
Order By: Relevance
“…Westbury et al (2000) review x-ray microBeam (XRMB) data and discuss the issues in kinematic event pattern analysis. Peng et al (2000), using a 'cushion-scanning' US technique for echocardiography, obtained the speed of tongue surface movement in the five stages of the liquid swallow they recognized: Mean values for all phases were 10.34 mm/sec, SD 2.10, with a range of 2.10 (minimum) to 32.43 (maximum), N = 165. They report the calculated single fastest speed as 305.67 mm/sec in the first phase of transport.…”
Section: (V) Tongue Movements In Feeding and Speechmentioning
confidence: 99%
“…Westbury et al (2000) review x-ray microBeam (XRMB) data and discuss the issues in kinematic event pattern analysis. Peng et al (2000), using a 'cushion-scanning' US technique for echocardiography, obtained the speed of tongue surface movement in the five stages of the liquid swallow they recognized: Mean values for all phases were 10.34 mm/sec, SD 2.10, with a range of 2.10 (minimum) to 32.43 (maximum), N = 165. They report the calculated single fastest speed as 305.67 mm/sec in the first phase of transport.…”
Section: (V) Tongue Movements In Feeding and Speechmentioning
confidence: 99%
“…Also the five phases of tongue muscle contraction described by c.l.peng 11,12 in 2002 according to each turn point between the two different directions at tongue movement cannot be used in cleft patients because the swallowing pattern is different in cleft patients, where the tongue contracts in various directions to various degrees to compensate for the palatal defect 13 . The mean change in FS following surgery was more in type 1 patients with complete cleft where the tongue contracts as a whole to seal the palatal defect efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…The probe was positioned in the sub mental region (Fig.1) in a sagittal plane and the contractions and relaxations of tongue musculature during swallowing of saliva in various phases of swallowing were assessed and recorded as m-mode images both before and after surgery 9,10,11,12 at the tip (phase -1, body(phase-2) and basal portions(phase-3) of the tongue.…”
Section: Methodsmentioning
confidence: 99%
“…It is noteworthy, however, that the USG of swallowing, as well as all the other imaging techniques, requires the speechlanguage therapist to have specific training with a specialized professional and to have basic knowledge of the appearance of the anatomic structures of the oropharynx, imaging procedures, and operation of the system (4) . There are studies that use the ultrasound of the tongue movement to characterize the oral phase of oropharyngeal swallowing (1,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) . Among these studies, some prioritized a qualitative description (1,(5)(6)(7) whereas others propose quantitative measures (8)(9)(10)(11)(12)(13)(14)(15) .…”
Section: Introductionmentioning
confidence: 99%
“…Among the studies that proposed the quantitative measures with the use of ultrasound (US) (8)(9)(10)(11)(12)(13)(14)(15) , it was observed that the adoption of different parameters, such as, duration of propulsion of the food bolus (sec); displacement of the lateral pharyngeal walls (cm); speed (mm/s), amplitude (mm), and duration (s) of the tongue movement during swallowing; in addition to the displacement of the hyoid bone, both in terms of duration (ms) and distance (mm).…”
Section: Introductionmentioning
confidence: 99%